2007
DOI: 10.1002/clc.9
|View full text |Cite
|
Sign up to set email alerts
|

A case report of simultaneous thrombosis of two coronary artery stents in association with clopidogrel resistance

Abstract: SummaryDespite aggressive antiplatelet therapy in the setting of PCI, the incidence of acute stent thrombosis remains approximately 0.5-2%. We report a patient with simultaneous thrombosis of two drug-eluting coronary artery stents, suggesting a systemic thrombotic state. Evaluation by optical platelet aggregometry revealed clopidogrel resistance, which was overcome at a higher drug dose. We aim to highlight the potential utility of platelet function analysis to guide therapy for patients in whom inadequate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Simultaneous multi-vessel ST is rare, but there were some reports concerning about this [11][12][13]. However, all of the previous reports were under the dual anti-platelet regimen [12,13] or association with clopidogrel resistance [11].…”
Section: Discussionmentioning
confidence: 98%
“…Simultaneous multi-vessel ST is rare, but there were some reports concerning about this [11][12][13]. However, all of the previous reports were under the dual anti-platelet regimen [12,13] or association with clopidogrel resistance [11].…”
Section: Discussionmentioning
confidence: 98%
“…A previous observational study [ 14 ] showed that clopidogrel resistance was present in 72.5% of patients admitted for repeated ACS, which suggests that HTPR likely plays an important role in recurrent ACS. Additionally, the phenomenon was reported as a leading cause of stent thrombosis (including left main-chain and multi-vessel stent thrombosis) in several clinical cases [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Insufficient Response To Adprb and The Risk Of Future Events...mentioning
confidence: 99%